Critical Pedagogy and young Arabic EFL learners: The Pedagogical and Social Implications of taking a Critical Approach in the Classroom - Nelson, Nadine Rachelle (Curtin University, 2019)
This study is an exploration into the pedagogical and social effectiveness of critical approaches when teaching a series of dialogic, problem posing lessons with young Arabic learners. This research also reports on the students’ attitudes towards the critical pedagogy lessons, and its impact on other literacy areas. This study presents another perspective within the ongoing debates surrounding the suitability and implementation of critical approaches and the EFL teaching field.